Analysis of Responsible Energy Consumer's Behaviour in the Context of REPowerEU Plan - Radu Ioan Petrariu; Marian Nastase; Gabriel Croitoru; Nicoleta Valentina Florea; Nicoleta Cristache; Mihaela Cristina Onica Ibinceanu (Amfiteatru Economic, 2023)
The planet's resources are finite and must be used rationally and responsibly to ensure a sustainable economy. On the basis of modern innovations and technologies, new sources of consumption or new ways to reduce the environmental impact of consumption can be found. Changes in the external environment and incredibly disruptive international events significantly influence consumer behaviour. In view of geopolitical changes, the energy crisis, Russia's invasion of Ukraine, and the instability of the energy market, the European Commission has drawn up a series of plans to ensure Europe's independence from Russia's energy resources. Research focusses on analysing the behaviour of responsible energy consumers as part of the objectives of REPowerEU and ANRE (Romanian Energy Regulatory Authority). To this end, 250 energy consumers were interviewed to observe their participation in reducing energy consumption and the measures implemented according to the REPowerEU plan. The consumers involved in the study have already implemented some important measures that have led to awareness of the negative consequences of geopolitical instability and the impact of natural resource consumption.
Keywords: O13; O44; Q01; Q2; Q4; 330; Responsible energy consumer behaviour; renewable sources; energy prices; social and demographic variables; energy consumption; energy policy; sustainable development.